2021
DOI: 10.1002/mrc.5210
|View full text |Cite
|
Sign up to set email alerts
|

Applicable and cost‐efficient microplastic analysis by quantitative 1H‐NMR spectroscopy using benchtop NMR and NoD methods

Abstract: In continuation of our work on the proof-of-concept that quantitative NMR spectroscopy may be a valuable tool in microplastic (MP) analysis and quantification, we present here investigations using low-field NMR spectrometers and nondeuterated solvents for the analysis of solutions of MP particles in suitable solvents. The use of low-field NMR spectrometers (benchtop NMR) that are considerably more cost-effective in terms of purchase and operating costs compared with high-field NMR spectrometers and the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Peez et al ). 23–26 For the calibration between 2.5 and 0.5 mg mL −1 , precision values greater than 98% were achieved for all polymers, whereas for the lower concentration range of 0.5–0.1 mg mL −1 precision values greater than 89% were still possible. Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Peez et al ). 23–26 For the calibration between 2.5 and 0.5 mg mL −1 , precision values greater than 98% were achieved for all polymers, whereas for the lower concentration range of 0.5–0.1 mg mL −1 precision values greater than 89% were still possible. Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Solvents for this study were selected according to several demands, listed in the next paragraph. These incorporate the necessary requirements for the selection of suitable solvents for simultaneous qNMR of multiple polymers and are based on considerations mentioned by Peez et al 23–26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MPs are analyzed through several stages, such as separation, identification, visualization, and quantification. Techniques used to characterize MPs are mainly microscopic (optical microscopy, fluorescence microscopy, Scanning Electron Microscopy—SEM, Transmission Electron Microscopy—TEM, and Atomic Force Microscopy—AFM) and spectroscopic (Fourier Transform Infrared Spectroscopy—FT-IR, Raman Spectroscopy—RS, Nuclear Magnetic Resonance—NMR) methods [ 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 ] ( Figure 7 ). They are mostly used to identify the polymeric composition of MPs, analysis of the shape, color, and size of the particles, as well as their quantity in test samples.…”
Section: Identification Methods Of Mpsmentioning
confidence: 99%
“…Moreover, Peez et al [ 23 ] showed that in the case of PET microplastics derived from different environments and subjected to various external conditions, qNMR methodologies can achieve very high analytical standards when associated with appropriate calibration and sampling procedures. It is worth noticing that other NMR techniques, such as 2D 1 H NMR diffusion-ordered spectroscopy (DOSY) [ 24 ], low field 1 H NMR [ 25 ], and 13 C multi cross polarization (CP) [ 26 ], were recently used to investigate microplastics.…”
Section: Introductionmentioning
confidence: 99%